Urinary Monocyte chemoattractant protein-1, Urinary Tumor Necrosis Factor-Like Weak Inducer of Apoptosis and Urinary Neutrophil Gelatinase-associated Lipocalin as predictors of lupus nephritis: a Systematic Review - Ana Miguel Nunes Barreiros Afonso (2022)
Objective: Systemic Lupus Erythematosus (SLE) is an autoimmune disorder that may have highly heterogeneous manifestations. Kidney affection, particularly Lupus Nephritis (LN), is a major complication of SLE and a robust determinant of associated morbidity and mortality. Early identification of renal involvement is critical to reduce the risk of irreversible kidney damage caused by inflammation and preserving renal function. Therefore, a deeper knowledge about the relationship of urinary chemokines and active LN may be useful for that propose and for noninvasively monitoring renal disease activity. The aim of this revision is to appraise the role of urinary Monocyte Chemoattractant protein-1 (uMCP-1), urinary Tumour Necrosis factor-like Weak inducer of apoptosis (uTWEAK) and urinary Neutrophil Gelatinase-associated lipocalin (uNGAL) in the detection of LN flare, three urinary markers previously selected, allowing a promptly and individualized therapy for the patient. Methods: A search of accessible digital literature was carried out in the databases PubMed, EMBASE and Scopus from 01 January 2015 to 31 December 2021, concerning the role of uMCP-1, uNGAL and uTWEAK on detection of LN flare and renal disease activity. Results: Among the 2500 studies retrieved, 10 were selected for further analysis. The results regarding the predictive value of urinary MCP-1, TWEAK and NGAL to LN flares, activity and chronicity index are inconsistent across the various studies. uNGAL levels showed a significant positive correlation with the rSLEDAI score and activity index, nevertheless results were inconsistent with respect to global SLEDAI score. uMCP-1 and uTWEAK levels showed a significant positive correlation with rSLEDAI score and SLEDAI and a greater association with the renal disease activity rather than with the degree of renal insufficiency. Conclusion: Urinary MCP-1, TWEAK and NGAL appear to be important biomarkers that reflect disease activity in SLE patients, mainly renal involvement and flare. However, the results were not consistent among studies. Therefore, further studies are needed to validate the use of these urinary biomarkers as diagnostic tools in LN and to predictive of flares or chronicity.